Flow cytometric mepacrine fluorescence can be used for the exclusion of platelet dense granule deficiency. (27th December 2019) - van Asten, Ivar; Blaauwgeers, Maaike; Granneman, Lianne; Heijnen, Harry F. G.; Kruip, Marieke J. H. A.; Beckers, Erik A. M.; Coppens, Michiel; Eikenboom, Jeroen; Tamminga, Rienk Y. J.; Pasterkamp, Gerard; Huisman, Albert; van Galen, Karin P. M.; et al.
Abstract: Background: δ‐storage pool disease (δ‐SPD) is a bleeding disorder characterized by a reduced number of platelet‐dense granules. The diagnosis of δ‐SPD depends on the measurement of platelet ADP content, but this test is time consuming and requires a relatively large blood volume. Flow cytometric analysis of platelet mepacrine uptake is a potential alternative, but this approach lacks validation, which precludes its use in a diagnostic setting. Objectives: To evaluate the performance of platelet mepacrine uptake as a diagnostic test for δ‐SPD. Patients/Methods: Mepacrine fluorescence was determined with flow cytometry before and after platelet activation in 156 patients with a suspected platelet function disorder and compared with platelet ADP content as a reference test. Performance was analyzed with a receiver operating characteristic (ROC) curve. Results: Eleven of 156 patients had δ‐SPD based on platelet ADP content. Mepacrine fluorescence was inferior to platelet ADP content in identifying patients with δ‐SPD, but both mepacrine uptake (area under the ROC curve [AUC] 0.87) and mepacrine release after platelet activation (AUC 0.80) had good discriminative ability. In our tertiary reference center, mepacrine uptake showed high negative predicitive value (97%) with low positive predictive value (35%). Combined with a negative likelihood ratio of 0.1, these data indicate that mepacrine uptake can be used to exclude δ‐SPD in patients with a bleeding tendency. Conclusion: Mepacrine fluorescence can be used as a screening tool to exclude δ‐SPD in a large number of patients with a suspected platelet function disorder.